Authority Reformulation Management of Natural and Biological Resources: Conservation District in Probolinggo - Indri Fogar Susilowati; Tamsil Tamsil; Elisabeth Septin Puspoayu; Hezron Sabar Rotua Tinambunan (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
The management of natural and biological resources must be carried out by the central and regional governments to seek financing for development. The management of natural and biological resources should synergize with its preservation and the environment. The common problem encountered when managing natural and biological resources lies in its improper management that caused damage to the environment such as doing disharmonize exploitation with environmental interest. Accordingly, This study employed a sociological juridical study to capture the implications of authority reformulation management of natural and biological resources of the conservation district in Probolinggo. The findings revealed that the management reformulation of Natural and biological resources Management results in the limitation of regional authority in managing their natural resources. This was certainly different from the concept mandated by regional autonomy. Thus, It is feared that this will affect the development plans carried out in the area, affecting the welfare of the community. As a conservation district, Probolinggo Regency has tried to optimize the regional potential in the development of conservation-minded areas. This commitment is written in regional regulations, regulating not only the use of natural and biological resources but the clarity of regional authority in managing these resources as well